Features of the diagnostics of the initial stage of generalized periodontitis by analysis of the indicators of the cytokine system - Ватаманюк, Н. В. (Actual Dentistry, 2018)
Рurpose: to determine the immunological criteria of the early stage of periodontitis in patients with generalized catarrhal gingivitis. Materials and methods. During implementation of this work, the study was conducted in two directions: clinical-radiological and immunological. All patients were divided into the following groups: the first included individuals suffering from acute generalized catarrhal gingivitis (32 people); in the second – with the diagnosis of the initial degree of generalized periodontitis (22 people). The control group consisted of 20 practically healthy volunteer donors of the same age and sex. Results of the study. In all patients with an initial degree of generalized periodontitis, there was a significant increase in the concentration of proinflammatory cytokines IL-1β and FNP-α on the background of a slight increase in the level of proinflammatory interleukin 4 (IL-4) in saliva. IL-1β indices were 2.2-fold, and FNP-α was 1.6 times higher than that of healthy donor groups. Conclusions. In the diagnosis of the early stage of the transition of generalized catarrhal gingivitis to periodontitis should lean on increase of hyperproduction of FNP-α and, especially, IL-1β whose size increases with the progression of changes in the gum tissue, as well as in the bone structures of the periodontal disease. Key words: catarrhal gingivitis, periodontitis, cytokines.